Economic Develompment Strategy Through Rural Areas A Case Study in Toba Samosir, North Sumatera, Indonesia - Dita Nurul Aini Mustika Dewi (Journal of Indonesian Applied Economics, 2020)
This study aims to analyze rural area development after Law No. 4, 2014, concerning villages. The new round of village development begins with the rights of recognition and the program of rural development by the Indonesian government. In this case, the village fund is the government flagship policy for village development, which considered to succeed in increasing the quality of people's lives through infrastructure, community empowerment, and the formation of rural areas. The development of rural areas is a center of growth, whereas focusing on the most developed areas in the disadvantaged region. To encourage the village economy, some policies used in rural areas by developing several villages that have different potential within locations. A method in this research is a case study that occurred over the past four years in Indonesia. In this case, the declining number of poor people become interesting. It happens because rural development, such as Ajibata, Toba Samosir, North Sumatra, Indonesia, can encourage regional development. The concept of rural areas relying on the coffee's attractiveness and coffee's processed as well as increasing the scale of coffee’s agricultural and the coffee's product value. Therefore, innovations in rural area development are significant to support regional economic development.